1991
DOI: 10.1002/eji.1830211136
|View full text |Cite
|
Sign up to set email alerts
|

Exact prediction of a natural T cell epitope

Abstract: T lymphocytes recognize their antigen as peptides associated with major histocompatibility complex (MHC) molecules. Peptides naturally presented by MHC class I molecules are uniform in length and have a specific motif, both defined by the respective MHC allele (Falk, K. et al. Nature 1991. 351:290). These allele-specific motifs should allow exact prediction of natural T cell epitopes. H-2Kb-restricted epitopes, for example, have a length of eight amino acid residues and conserved anchor residues at positions 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
235
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 410 publications
(243 citation statements)
references
References 12 publications
5
235
0
2
Order By: Relevance
“…Assuming that bona fide MHC-dependent peptides were present at very low concentrations, we reasoned that they would be missed in MS analyses due to the presence of a multitude of other, more abundant peptides. In fact, control experiments showed that a synthetic MHC peptide spiked into urine is not reproducibly detected at concentrations below 10 À 11 M. Therefore, we developed a highly specific model system based on the well-studied H2-K b -presented peptide SIINFEKL corresponding to amino-acid residues 257-264 of chicken ovalbumin (OVA) 40,41 . The transgenic mouse line B6/OVA þ expresses a cell surface protein composed of the entire chicken ovalbumin sequence and a transmembrane sequence under the control of the chicken b-actin promoter in all organs.…”
Section: Isolation and Analysis Of Urinary Peptides By Mass Spectromementioning
confidence: 99%
“…Assuming that bona fide MHC-dependent peptides were present at very low concentrations, we reasoned that they would be missed in MS analyses due to the presence of a multitude of other, more abundant peptides. In fact, control experiments showed that a synthetic MHC peptide spiked into urine is not reproducibly detected at concentrations below 10 À 11 M. Therefore, we developed a highly specific model system based on the well-studied H2-K b -presented peptide SIINFEKL corresponding to amino-acid residues 257-264 of chicken ovalbumin (OVA) 40,41 . The transgenic mouse line B6/OVA þ expresses a cell surface protein composed of the entire chicken ovalbumin sequence and a transmembrane sequence under the control of the chicken b-actin promoter in all organs.…”
Section: Isolation and Analysis Of Urinary Peptides By Mass Spectromementioning
confidence: 99%
“…The 0h-, 8 h-and 48h-DC were loaded with the peptide SIINFEKL [34] at a concentration (100 nM) that in preliminary experiments (peptide range 1-1000 nM) favored the induction of the highest percentage of Tc2 cells, and cultured together with naive OT-1 cells, a homogeneous population of TCR-transgenic CD8 + cells [35], in the presence or absence of optimal amounts of IL-12 or IL-4. Seven days later, cells were collected and assessed for cytokine production by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we assessed the capacity of DC at various activation stages to induce polarization of a transgenic T cell population with a different specificity, i.e. cells from TCR7 mice expressing a TCR specific for the epitope 33-41 of lymphocytic choriomeningitis virus (LCMV) glycoprotein 1 (gp [33][34][35][36][37][38][39][40][41] ) [37,38]. In this set of experiments we also tested CpG as pro-maturation stimulus (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a well established phenomenon in the T-cell antigen complex, MHC ''peptide receptor'' system that encodes the intracellular presence of a specific protein via a short peptide on its surface. [127][128][129] In addition, the sequence of ''hydrophobic fingers,'' suggested as a physical expression of the condensed protein code in MHC peptides 128 may be related to the ligand-protein interactions pre- dicated on similarities in their hydrophobic autocorrelation eigenvectors. 1,4,7,16 A similar manifestation of short peptide signaling of a large protein in immunological systems is evidenced by the successful use of protein analogue peptides as ''protein mimetic'' short peptide antigens.…”
Section: Discussionmentioning
confidence: 99%